Second generation European corn borer injury and Irish potato physiology, yield, and quality - Ziems, Jesse R.; Hoback, W. Wyatt; Higley, Leon G.; Hunt, Thomas E.; Fernandes, Odair A. [UNESP]; Bastos, Cristina; Bueno, Adeney de Freitas (Amer Soc Agronomy, 2008)
European corn borer (ECB) [Ostrinia nubilalis (Hubner)] (Lepidoptera: Crambidae) is known to infest Irish potato (Solanum tuberosum L.) but only causes economic damage during the first generation in East Coast potato producing areas. However, in Nebraska, second generation ECB infest potato plants during the bulking period and may reduce yield and/or potato quality. Experiments were conducted in 2001, 2002, and 2003 to examine physiological and yield effects of second generation ECB injury to potato in Nebraska. Pike, Atlantic, and three Frito Lay proprietary varieties (FL1867, FL1879, and FL1833) were used. Experimental plots were infested with four ECB egg masses per plant to simulate ECB infestation by second-generation larvae; controls received no egg masses. Photosynthetic rates, tuber weights, tuber size grades, solids, and fry quality were measured. Potato plants with ECB infestation had significantly reduced photosynthetic rates on ECB-infested stems and on uninfested stems on the same plant when larvae were in the fifth instar. When insects were in the fourth instar, photosynthetic rates were reduced only on ECB-infested stems. In 2001, ECB infestation reduced the average mass of large tubers and increased the amount of small tubers in FL1867 and FL1879. In 2002, significant yield reductions were not observed. Across both years, ECB-infested plots produced fewer large (65- to 100-mm diam.) tubers than control plots. Other tuber properties and chip qualities were unaffected. This study indicates that second generation ECB infestation of approximately 30% infested plants results in economic loss for some chipping varieties and affects tuber bulking. In contrast to east coast growers, Midwest potato farmers must be concerned with second generation ECB.